Peningkatan Kemampuan Membaca Pemahaman Siswa Melalui Metode Pembelajaran Cooperative Integrated Reading And Composition (CIRC) - Azella Mierey Salsabila; Riga Zahara Nurani; Fajar Nugraha (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2023)
This research was motivated by the low reading ability who had not reached the minimum completeness criteria (KKM), which was 75. Class VI C at SD Negeri Mugarsari as many as 20 students are the sample in this study. The purpose of this research is through the Cooperative Integrated Reading and Composition (CIRC) method, students' reading comprehension skills can be increased. This research method uses a class action research design owned by Kemmis and Mc Taggart, with research planning divided into four stages, namely: 1. Planning 2. Implementation 3. Observation 4. Reflection and carried out in 2 cycles. The research implementation was divided into three stages, namely opening activities, core activities, and closing activities, and using the steps of the Cooperative Integrated Reading and Composition (CIRC) method. The results of the research in the first cycle obtained an average value of 74 with the percentage of students who had completed it by 50% and students who had not completed it was 50%. Furthermore, in the second cycle an avarage score of 87 was obtained with the percentage of students who had not completed were 15% and those who had completed 85%. Based on the results of this study it can be concluded that the reading comprehension ability of class VI C students at SD Negeri Mugarsari can be increased through the Cooperative Integrated Reading and Composition (CIRC) method.